2016
DOI: 10.1093/intqhc/mzw095
|View full text |Cite
|
Sign up to set email alerts
|

Providing antenatal corticosteroids for preterm birth: a quality improvement initiative in Cambodia and the Philippines

Abstract: ObjectiveTo determine whether a simple quality improvement initiative consisting of a technical update and regular audit and feedback sessions will result in increased use of antenatal corticosteroids among pregnant women at risk of imminent preterm birth delivering at health facilities in the Philippines and Cambodia.DesignNon-randomized, observational study using a pre-/post-intervention design conducted between October 2013 and June 2014.SettingA total of 12 high volume facilities providing Emergency Obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“… 36 A quality improvement initiative for ACS use comprising a technical update followed by an audit of and feedback on ACS data led to an increase in ACS coverage, knowledge score, and confidence of HCPs, as well as a complete recording of ACS data in the Philippines and Cambodia. 37 Our study identified the need for establishing a quality improvement and monitoring system for ensuring appropriate use of ACS in line with the 2015 WHO recommendations.…”
Section: Discussionmentioning
confidence: 88%
“… 36 A quality improvement initiative for ACS use comprising a technical update followed by an audit of and feedback on ACS data led to an increase in ACS coverage, knowledge score, and confidence of HCPs, as well as a complete recording of ACS data in the Philippines and Cambodia. 37 Our study identified the need for establishing a quality improvement and monitoring system for ensuring appropriate use of ACS in line with the 2015 WHO recommendations.…”
Section: Discussionmentioning
confidence: 88%
“…While some health systems and organizations have been successful at improving performance through such QI approaches [ 3 5 ] many are less successful. Some researchers have explored why some organizations are less able to deliver improved performance and argue that a systematic approach to developing improvement capability is required [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the 46 included studies were conducted in 32 countries in Region of the Americas (6 countries: United States of America [ 24 , 40 – 51 ], Canada [ 44 , 52 54 ], Mexico [ 55 , 56 ], Ecuador [ 56 ], El Salvador [ 56 ], and Uruguay [ 56 ]), Western Pacific Region (7 countries: Australia [ 23 , 57 63 ],New Zealand [ 58 64 ], Vietnam [ 22 ], Singapore [ 65 ], Taiwan [ 66 , 67 ], Cambodia [ 68 ], and Philippines [ 68 ]), European Region (4 countries: United Kingdom [ 69 72 ], Ireland [ 73 ], Sweden [ 74 ], and France [ 75 , 76 ]), Southeast Asia Region (4 countries: Thailand [ 77 ], Bangladesh [ 22 ], India [ 22 , 78 ], and Nepal [ 22 ]), Eastern Mediterranean Region (2 countries: Afghanistan [ 22 ] and Pakistan [ 22 ]), Africa region (9 countries: Cameroon [ 22 ], Democratic Republic of Congo [ 22 , 79 ], Kenya [ 22 ], Malawi [ 22 , 79 81 ], Nigeria [ 22 , 79 ], Uganda [ 22 , 79 ], Ethiopia [ 79 ], Sierra Leone [ 79 ], and Tanzania [ 79...…”
Section: Resultsmentioning
confidence: 99%